Spotlight - Cariou, Len; Chuck, Wendy; Countryman, Michael; Creighton, Michael Cyril; Crudup, Billy, 1968-; Guilfoyle, Paul; Huff, Neal; James, Brian D'Arcy; Keaton, Michael, 1951-; McAdams, Rachel, 1978-; McCarthy, Tom, 1966-; Ruffalo, Mark; et al. (2016)
The riveting true story of the Pulitzer Prize-winning Boston Globe investigation that would rock the city and cause a crisis in one of the world's oldest and most trusted institutions. When the newspaper's tenacious 'Spotlight' team of reporters delve into allegations of sexual abuse of children by clergy in the Catholic Church, their year-long investigation uncovers a decades-long cover-up at the highest levels of Boston's religious, legal, and government establishment.